2006
DOI: 10.1016/j.desal.2006.03.295
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of bio-foulants in the membrane bioreactor

Abstract: The pilot submerged MBR (PSMBR) was operated with sewage to investigate the characteristics of soluble membrane foulants. Molecular weight distributions of soluble materials were analyzed and molecular weight fractionations were conducted as protein and carbohydrate compositions. Soluble materials of MW above 40 kDa were rejected by membrane, even if 0.4 μm pore size of microfiltration was used. Fourier transform infrared (FTIR) spectra and scanning electron microscope (SEM) were applied to monitor fouled memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…where it was found that a MF membrane with pore size of 0.4 μm could retain biopolymers of MW as low as 40 kDa [40]. Electrostatic repulsion may be a factor in causing the rejection of biopolymers of sizes smaller than the physical pore size of membranes [41].…”
Section: Discussionmentioning
confidence: 99%
“…where it was found that a MF membrane with pore size of 0.4 μm could retain biopolymers of MW as low as 40 kDa [40]. Electrostatic repulsion may be a factor in causing the rejection of biopolymers of sizes smaller than the physical pore size of membranes [41].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are numerous EPS extraction methods, but there is no standard (or generalized) method for extraction. Some of the EPS extraction strategies include cation exchange resin, centrifugal operation with formaldehyde, and heating techniques . Previous research has demonstrated that formaldehyde extraction is the most effective technique to extract high concentrations of EPS, though the heating method is sometimes preferred due to its simplicity…”
mentioning
confidence: 94%
“…EPS are produced by bacterial metabolisms (e.g., bacterial excretion, secretion, shed from the cell surface or cell lysis, and sorption), which consist of insoluble materials. EPS are gel‐like and are a highly hydrated matrix for the immobilization of the microorganisms . EPS create a three‐dimensional protective layer around the bacteria against the external stress and toxicity to such an extent that they provide a significant barrier to the permeate flow.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The flux decline due to biofouling generally occurs by microbial cell attachment or the excretion of cell byproducts (extracellular polymeric substances; EPS) . Furthermore, it has been posited that biofouling studies are more important when membrane technologies are applied to biological processes, as is the case for MBR processes …”
Section: Introductionmentioning
confidence: 99%